SUSTAINABLE LIVELIHOODS THROUGH COMMUNITY EMPOWERMENT IN BUMIAJI, BATU CITY, EAST JAVA - Handoko, Setiyo Yuli; Puspita, Yeni (IPTEK Journal of Proceedings Series, 2019)
The study objective is to analyze sustainable livelihoods (farmers conditions ; social, economic, and income) through community empowerment in the Sumber Brantas Village, Bumiaji, Batu City, East Java Province. The community empowerment program is a program to change plant commodities from garlic plants to potato plants. The research method is qualitative research. The key informants this study include the chairperson and members of Farmer Group "Anjasmoro Jaya Abadi 04". The results of the study include the first farmers to carry out the adaptation process. Second, farmers imitate the process, finally the farmers make the transition from garlic plants to potato crops. The change in livelihood from garlic farmers to potato farmers has an impact on economic life, their incomes have increased. Social life, in terms of the level of community education which is starting to change and high causes their social level to be better, cultural life, people who used to always know "mutual cooperation" on the land of fellow peers, help each other, but for now due to changes in income levels and they have been able to pay outside workers.